Basic Study of Copyright for Batik Wood Artists in Gunung Kidul, Yogyakarta - Subiyantoro, Slamet; Susilaningsih, Susilaningsih; Maryono, Dwi (Faculty of Law, Universitas Sebelas Maret, 2017)
The aims of this research is to explain the batik wood artists level of understanding of Copyright as part of Intellectual Property as stipulated in Act Number 19 Year 2002. The research was conducted with descriptive qualitative approach and the data were collected using questionnaires from 65 batik wood artists that were selected randomly from 673 artists in Gunung Kidul. The data is also completed with interviews from main informants, and observation results and content analysis results. The data validation was done use source triangulation techniques to obtain data that reflecting facts. Data analyzed with interactive model in cycle with stages data collection, data reduction, data presentation and data verification. The results show that the low implementation of copyright registration is not only due to the lack of artists in understanding the Copyright, but rather from the influence of socio – cultural aspects of society that are collective. Thus, emphasizing the moral aspect of the formal aspects such as Copyright that are part of the western culture. The Copyright Act No. 19 Number 2002 is the revision of previously Copyright Act which has not provided a proportional space for Moral Rights compared to Copyright which tends to the economic aspects.